The Confrontation Of Pop Culture And Revolution: Iran Case - Wafi, Mahmud (Universitas Islam Negeri Raden Intan Lampung, 2021)
The world community is undergoing a fundamental shift or transformation in social and cultural order. A transformation from modernism to post-modernism. This can be seen from the growing trend of pop culture: film, fashion, video, music, communication, technology, and others. Responding to this global transformation, Iran seems to be trying to ward off the pop culture attack. Iran saw that it could threaten the principles of its revolution. Iran’s refusal received a negative response from Iranian society, especially young people. A group that can be said to have been born from the womb of post-modernism. Various criticisms and resistances were also shown to the Iranian revolutionaries who were very firm in upholding the principle of wilayat al-faqih. This research is focused on reading and examining the phenomenon of resistance of the Iranian youth to the government and religious authorities using a qualitative approach. Furthermore, the author also highlights the extent and how the Iranian Revolutionary Guards ward off the global pop culture epidemic, in order to secure the principles of their revolution. This research shows that the trend of pop culture is an alternative for resistance to the authorities of the Revolutionary Guards and strengthens the position of the reformist camp. In addition, the panic of the revolutionary guard to maintain the status quo has trapped them in repressive actions that are contrary to the spirit of the revolution itself.